ORGAN DONATION AND TRANSPLANTATION IN RUSSIAN FEDERATION IN 2017 10TH REPORT OF THE NATIONAL REGISTRY - S. V. Gautier; S. M. Khomyakov (Вестник трансплантологии и искусственных органов)
Aim. To analyse the status and trends in the development of organ donation and organ transplantation in the Russian Federation according to 2017 data.Materials and methods. The survey of heads of transplantation centers  was conducted. A comparative analysis of the data obtained in the dynamics of years, between individual subjects of the Russian Federation, the centers of transplantation is performed.Results. According to the register in 2017 in Russia there were only 41 centers for kidney transplantation, 24 liver and 16 hearts. The waiting list for kidney transplantation in 2017 included 5,531 potential recipients, which is approximately 13.8% of the total number of 40,000 patients receiving dialysis. The level of donor activity in 2017 was 3.8 per million of the population, while the share of multiorgan seizures was 66.5%, the average number of organs received from one effective donor was 2.8. In 2017, the level of kidney transplantation was 8.0 per million of the population, the liver transplantation index was 3.0 per million of the population; the rate of heart transplantation is 1.7 per million of the population. In 2017 the number of transplants in Russia increased by 11.3% compared to 2016. There are 11 transplantation centers on the territory of Moscow and the Moscow Region, and half of all kidney transplants and 70% of all liver and heart transplantations are performed. The number of patients with transplanted organs in the Russian Federation is approaching 13,000.Conclusion. In the Russian Federation there is a strong tendency to increase the number of effective donors and to increase the number of organ transplants, and the number of transplant centers is also increasing. In recent years, the country has created prerequisites for the development of organ donation and transplantation: the regulatory and legal framework, public donation funding, material and technical base, etc. In the coming years, positive experience and organizational patterns of organ donation and transplantation from successful regions in Other subjects of the Russian Federation for building effective programs. The leading role in this process should be played by the Academician V.I. Shumakov Federal Research Center of Transplantology and Artiﬁ cial Organs.